Psychological well-being of elderly people: the social factors - Kovalenko, Olena Hryhorivna; Spivak, Lyubov Mykolaivna (Social Welfare: Interdisciplinary Approach, 2018)
The article discusses the social factors of psychological well-being of elderly people. Psychological well-being is a personal phenomenon. It forms in the process of human activity and in the system of people`s real relationships with surrounding objects. In old age psychological well-being is determined by different factors. The social factor is one of them. It has been found that higher levels of psychological well-being have those elderly people who do not feel themselves lonely, who have enough opportunities to communicate with other people, who take part in a social life, who live with relatives. Specifics of everyday activity in older age are not substantially related to psychological well-being.